2009
DOI: 10.1007/s10310-008-0109-1
|View full text |Cite
|
Sign up to set email alerts
|

Reproduction of a Robinia pseudoacacia population in a coastal Pinus thunbergii windbreak along the Kujukurihama Coast, Japan

Abstract: We investigated reproduction of the clonal tree Robinia pseudoacacia in a Pinus thunbergii windbreak.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 30 publications
0
36
0
2
Order By: Relevance
“…This finding is consistent with our observations. Also, in case of Robinia pseudoacacia which reproduces both sexually and asexually (Kowarik 1996, Jung et al 2009, Kurokochi et al 2010, some studies have shown that new horizontal roots are supplied with photosynthates from the mother plant or ramet for a few years only and that resource translocation between neighboring ramets within the same clone ceases after several years (Jung et al 2009). This might explain the advantage of root sprouts in the initial period of their development.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with our observations. Also, in case of Robinia pseudoacacia which reproduces both sexually and asexually (Kowarik 1996, Jung et al 2009, Kurokochi et al 2010, some studies have shown that new horizontal roots are supplied with photosynthates from the mother plant or ramet for a few years only and that resource translocation between neighboring ramets within the same clone ceases after several years (Jung et al 2009). This might explain the advantage of root sprouts in the initial period of their development.…”
Section: Discussionmentioning
confidence: 99%
“…Black locust digunakan pada proyek reklamasi hutan di daerah arid Iran (Moshki dan Lamersdorf, 2010); untuk restorasi pada lahan marginal yang ketersediaan air dan N tanahnya rendah di Loess Plateau dan daerah arid lainnya di Cina , serta digunakan sebagai pupuk alami bagi pohon pinus di hutan pantai Jepang (Jung et al, 2009). Black locust yang awalnya digunakan untuk tujuan reklamasi dan produksi di beberapa negara persebarannya, saat ini telah berpotensi menjadi invasif.…”
Section: Pendahuluanunclassified
“…Nuclear microsatellite (nSSR) markers with high polymorphism can contribute to the analysis of parenthood, kinship, and population differentiation (Kurokochi and Hogetsu 2014). The capability of asexual reproduction of woody species via adventitious roots could form large genets with a lot of ramets (Gyokusen et al 1991, Kowarik 1995, Ogawa and Hukusima 1996, Kurokochi et al 2010, and genets can be readily detected with high polymorphism nuclear DNA markers (Jung et al 2009, Kurokochi et al 2010). ABI 3130 automated DNA sequencer (Applied Biosystems, Foster City, CA, USA), and their fragment sizes were analyzed with a GeneMapper software (Applied Biosystems).…”
Section: Site Patch and Sample Collectionmentioning
confidence: 99%